Implementation of Participatory Planning and Development in the Revitalization of Cadika Park, Medan City - Nasution, Chairika; Sigalingging, Erna Lupita; Putri, Dini Ayunda (Mahesa Research Center, 2025)
This study aims to analyze the implementation of participatory planning and development in the revitalization of Cadika Park in Medan City using the Implementation Theory approach according to George C Edwards III. This study uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. Data analysis follows the interactive model of Miles and Huberman through the stages of data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that the implementation of participatory planning and development in the revitalization of Cadika Park in Medan City is not optimal. Based on the Theory of George C. Edwards III, it was found that (1) communication between agencies is less effective, and community participation is minimal, hampering the effectiveness of implementation. (2) Human resources and budget are adequate thanks to CSR support from the City Government. (3) DISPORA's disposition shows a positive commitment, but post-project supervision is weak, reducing the sustainability of maintenance. (4) A flexible bureaucratic structure supports implementation, but post-project supervision still needs to be improved. More effective communication, wider community participation, and ongoing supervision are needed for optimal results.